2013
DOI: 10.1021/jp400616c
|View full text |Cite
|
Sign up to set email alerts
|

On the Condensed Phase Ring-Closure of Vinylheptafulvalene and Ring-Opening of Gaseous Dihydroazulene

Abstract: Dihydroazulenes are interesting because of their photoswitching behavior. While the ring-opening to vinylheptafulvalene (VHF) is light induced, the back reaction is known to proceed thermally. In the present paper, we show the first gas phase study of the ring-opening reaction of 2-phenyl-1,8a-dihydroazulene-1,1-dicarbonitrile (Ph-DHA) by means of time-resolved photoelectron spectroscopy which permits us to follow the ring-opening process. Moreover, we investigated s-trans-Ph-VHF in a series of transient absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…Upon UV irradiation in solution these compounds undergo a ring‐opening reaction to their more strongly colored metastable form, vinylheptafulvene (VHF), which can exist in syn ‐ and anti ‐conformations (Figure ) . Based on computational analysis, it was proposed that the photochromic reaction occurs via a zwitterionic transition state . This reaction is attractive due to the anticipated large structural difference between DHA and anti ‐VHF, and the possibility for fine‐tuning of the switch by chemical substitution .…”
Section: Introductionmentioning
confidence: 99%
“…Upon UV irradiation in solution these compounds undergo a ring‐opening reaction to their more strongly colored metastable form, vinylheptafulvene (VHF), which can exist in syn ‐ and anti ‐conformations (Figure ) . Based on computational analysis, it was proposed that the photochromic reaction occurs via a zwitterionic transition state . This reaction is attractive due to the anticipated large structural difference between DHA and anti ‐VHF, and the possibility for fine‐tuning of the switch by chemical substitution .…”
Section: Introductionmentioning
confidence: 99%
“…IRC calculations revealed that the conrotatory and disrotatory TSs both connect to DHA and VHF, see the Supporting Information for details. Earlier computational work includes a single TS, which we identify as the Disrot‐TS . Our identification of these two TSs has resulted in inclusion of these in the theoretical work in a number of recent publications …”
Section: Resultsmentioning
confidence: 99%
“…Earlier computational work includes as ingle TS, which we identify as the Disrot-TS. [9,25,26] Our identification of these two TSs has resulted in inclusion of these in the theoretical work in an umber of recent publications. [22,[27][28][29] The Gibbs energy differences between the lowest energy VHF conformer and TS, DG VHF!TS ,a re shown in Figure 2f or each investigated DHA/VHF system in vacuum and the four solvents (benzene, tetrahydrofuran, acetone, and acetonitrile).…”
Section: Resultsmentioning
confidence: 99%
“…Functionalization of position 2 on the DHA skeleton has been most extensively explored. 5,6,[9][10][11][12][13][14][15][16][17][22][23][24][25][26][27][28] Aromatic groups are the substituents most widely incorporated, but few examples with methyl group on C-2 or cyclopentyl between C-2/C-3 have also been reported. 22 As described in the introduction (Scheme 3), the syntheses have followed either: (i) the [8+2] cycloaddition protocol, (ii) the route via nucleophilic addition of acetophenones to tropylium, followed by a Knoevenagel condensation with malononitrile, or (iii) an initial Knoevenagel condensation followed by reaction with tropylium species.…”
Section: Reactivity and Functionalization Of The Five-membered Ring Omentioning
confidence: 99%
“…8,9 This is in line with a suggested mechanism that involves a zwitterionic transition state, with a positively charged seven-membered ring and a negatively charged malononitrile moiety. 10 The longest-wavelength absorption maxima of DHA 1 and VHF 2 are at 353 and 470 nm, respectively, in acetonitrile ( Figure 1). 9 In this solvent, the quantum yield of the ring-opening reaction from 1 to 2 is 0.55 8 , and the rate constant for the back-reaction is 5.36 x 10 -5 s -1 .…”
Section: Introductionmentioning
confidence: 98%